The VOICE study – a before and after study of a dementia communication skills training course - Fuh, Jong-Ling; O’Brien, Rebecca; Goldberg, Sarah. E.; Pilnick, Alison; Beeke, Suzanne; Schneider, Justine; Sartain, Kate; Thomson, Louise; Murray, Megan; Baxendale, Bryn; Harwood, Rowan H. (Public Library of Science, 2018)
Background